Artistic and ideological features in the epic story “Leyli and Majnun”: based on the versions by Nizami and Shahkarim - Kudaibergenova, G.K. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The epic story of “Leyli and Majnun” is a prominent work of Eastern literature, renowned as a symbol of love and tragedy. This article provides a comparative analysis of the epic story of “Leyli and Majnun” according to the versions by Nizami and Shahkarim, focusing on their artistic and ideological characteristics. The study explores the different approaches to the theme of love in the works of both poets, the depiction of social constraints and human freedom, as well as the interplay between Eastern literary traditions and Kazakh worldview. Special attention is given to the poetic language of Nizami’s version and the national coloration added in Shahkarim’s translation, alongside the philosophical depth of thought. The purpose of this research is to explore the creative harmony between Eastern and Kazakh literature through the two versions of the epic "Leyli and Majnun." The objectives include uncovering the main ideas, philosophical, and moral values of the poem as seen in Nizami’s and Shakarim’s interpretations; comparing the concepts and perspectives on love across different eras and cultures; analyzing the poetic style and structural features in the works of the two poets; studying the origin of the poem and its connection to the cultural and social conditions of its time.